Aurolab Aqueous Drainage Implant (AADI): Review of Indications, Mechanism, Surgical Technique, Outcomes, Impact and Limitations. (17th November 2022) - Sisodia, Vishwendra Pratap Singh; Krishnamurthy, Rashmi
ABSTRACT: Purpose: The purpose of this review is to place together all the knowledge available on aurolab aqueous drainage implant (AADI) in one place for the benefit of all glaucoma specialists who are interested in low-cost implants in developing world with desired results. Methods: A comprehensive literature search was done on AADI and its use in glaucoma management. 35 results were obtained from the literature search. Out of these 35, 2 were commentaries, 6 were case reports and rest 27 were studies (prospective and retrospective) discussing the surgical outcomes, modifications and comparison of AADI with other glaucoma drainage devices (GDDs). Out of these, 2 commentaries were excluded and rest 33 articles were included, cited and discussed appropriately in this review. Results: AADI resulted in a significant reduction in the intra ocular pressure (IOP) and also in the number of antiglaucoma medications. AADI can be implanted alone or combined with cataract surgery. It was found to be beneficial in both pediatric and adult refractory glaucoma. There was no significant difference seen in the pre and post operative visual acuity. But AADI was also associated with various hypotony related and tube related early and late onset complications. Some of these complications were managed conservatively and some needed surgical intervention. Conclusions: AADI is a low-cost non-valved GDD with successful results in both adult as well as pediatric refractory glaucomas. Early and late onset complications are common and can be managed with appropriate and timely medical or surgical intervention.